PEMBUATAN APLIKASI ABSENSI DALAM RANGKA MENINGKATKAN KINERJA DAN EFISIENSI ADMINISTRASI PADA BIMBEL RUMAH PINTAR KAK WELL DI KOTA PADANG - Sanda Patrisia Komalasari; Nurul Ulfah Primadini Abdalliza Zikra; Hanifah Shabrina; Puti Rahmayani; Putri Triani Ma’ruf; Vika Ramadhani (Jurnal Hilirisasi IPTEKS, 2024)
This service activity aims to help Kak Well's Smart Home Tutoring record attendance data that was previously done manually. Manual attendance recording could be more efficient, often produces inaccurate and non-real-time reports and results in difficulties in monitoring employee and student attendance. The solution provided by the Service Team is to develop an attendance application using Microsoft Access. This application has easy-to-use features, including a main page for navigation, employee and student data input, daily attendance input, and preparation of attendance reports for employees and students. With these features, the attendance application can replace inefficient manual methods and increase the accuracy of attendance data. This service activity results in the implementation of the attendance application at Kak Well's Smart Home Tutoring. This application allows attendance recording to be carried out better, more effectively, and efficiently than the previous manual method. Apart from that, the service team also provides training and assistance in operating the application that has been created, ensuring that the Kak Well Smart Home Tutoring staff can use it well. In conclusion, the developed attendance application succeeded in increasing the efficiency and accuracy of recording attendance at Kak Well's Smart Home Tutoring. The training ensures that the application can be used optimally by the Tutoring team, making the attendance process more organized and reliable.